Meningkatkan Kesadaran Masyarakat Akan Pentingnya Perilaku Hidup Bersih Dan Sehat PHBS Dengan Gotong Royong Di Desa Padang Garugur - Habibah Nasution; Roma Diana; Anggi Saputra; Putri Khodijah; Nur Hadimah; Elwina Sari; Riski Sapitri; Sulaiman Lubis; Muhammad Randi (Institut Teknologi dan Bisnis Semarang, 2024)
Clean and Healthy Living Behavior (PHBS) is an important component in maintaining the health of a person and society as a whole. It is very important to realize the benefits of PHBS in preventing disease and improving quality of life. The purpose of this article is to examine various ways and efforts that can be made to increase public awareness of the importance of PHBS. It is hoped that by using a holistic and sustainable approach, such as outreach campaigns, education, and building adequate sanitation infrastructure, it will be possible to create a strong PHBS culture in society. It is hoped that the implementation of this strategy will have a positive effect on improving overall community health (Rahmanisa, S., Kurniawaty, E., & Susantiningsih, T, 2015).PHBS is a lifestyle that prioritizes cleanliness of the body and the surrounding environment which must be used in daily activities to improve the quality of life and health based on the will of the yourself and also the environment. One of the efforts we can make to realizing PHBS in the surrounding environment, namely, the community must maintain it cleanliness and health because it will affect the quality of life. In terms of Currently, the people of Padang Garugur Village are still less aware of cleanliness the environment around them. This is shown by the large amount of rubbish piled up on roadsides and around rivers or public baths. Factor The cause of this lack of cleanliness is a lack of cooperation between citizens, population density, and also the presence of modernization factors, which has an effect on reducing the sense of togetherness of citizens, as is the case in mutual cooperation activities. Because of this, efforts are needed to encourage people to maintain cleanliness and health in the environment around. To improve the quality of clean and healthy life of village communities Padang Garugur, the KKN program was used to carry out these activities. Some of the activity programs carried out include: cleaning mosque, clearing the road leading to the public baths cleaning channels and water storage tanks in public baths, and also cleaning the village public cemetery, as well as cleaning the road area does not hinder the driver.